Analisis kesalahan penggunaan huruf kapital dan tanda baca dalam menulis karangan sederhana peserta didik kelas III Sekolah Dasar - Indri Purnamasari; Retno Winarni; Jenny Indrastoeti Siti Poerwanti (Universitas Sebelas Maret, 2024)
The primary objective of this investigation is to outline the varieties and reasons behind errors in employing capital letters and punctuation found in basic essays penned by third-grade students. Employing a descriptive qualitative research approach, the study seeks to scrutinize and analyze the mistakes made in the application of capitalization and punctuation within the students' essays. The study enlisted the participation of 27 third-grade students and a third-grade teacher. Various data collection methods, such as observation, interviews, and document analysis, were employed to gather comprehensive insights into the nature of these errors. The findings of this investigation highlighted various instances of errors in the application of capital letters and punctuation marks. The highest frequency of errors in capitalization was observed in the initial letter at the commencement of sentences, accounting for 32.04%, whereas the least frequent errors were associated with the use of personal pronouns, totaling 9.2%. Additionally, errors related to punctuation marks were predominantly linked to period punctuation, with a frequency of 63.10%, while the least common errors were observed in the utilization of period comma marks, constituting 36.90%. The primary root cause of these errors appears to stem from learners' writing practices deviating from language norms, coupled with a tendency to forget and a lack of precision during the writing process.